Parenting Style dalam Al-Qur’an Studi terhadap Kisah Nabi Ibrahim dalam Q.S. Ash-Shaffat:100-107 dalam Tafsir Al-Azhar - Siregar, Muhajiroh Alya (Lembaga Yasin AlSys, 2023)
The Qur'an as a guide for human life has given instructions on how parenting or upbringing and educating children should be. This study discusses the parenting style of the Prophet Ibrahim towards his children contained in Q.S ash-Shaffat verses 100-107 according to the interpretation of Buya HAMKA in Tafsir Al-Azhar, with the aim of providing explanations and examples that can be emulated by parents on how to raise Islamic children. in order to give birth to a generation that is good, independent, confident and has good morals according to what is taught by the Al-Qur'an. This study uses a qualitative method, by collecting phenomena or data regarding parenting in depth, and also using the library research method with a descriptive analysis approach, namely finding facts, ideas and data that have been collected and processed. from the thoughts of Buya HAMKA in Tafsir Al-Azhar with the Tahlili method, which explains the Qur'an in detail. As well as other literary sources that have been tested. The results of this study indicate that Prophet Ibrahim's parenting was colored by his efforts to approach himself to Allah by praying so that he would be blessed with righteous children, instilling obedience and obedience to Allah, communicating with children as well as being friendly and hard working.